Myocardial ischemia – reperfusion injury - S. V. Salo; V. O. Shumakov; S. S. Shpak; V. V. Tokhtarov (Zaporožskij Medicinskij Žurnal)
Aim. To summarize and broaden the idea about mechanisms of acute coronary insufficiency development and pathophysiological features of myocardial reperfusion injury.